Differential expression of HTR2A and MAOA genes in the prefrontal cortex and hypothalamus of suicide victims from Mexican population. (1st May 2022) - Ramos-Rosales, Daniel; Méndez-Hernández, Edna; Salas-Pacheco, José; Salas-Leal, Alma; Urtiz-Estrada, Norma; Barraza-Salas, Marcelo; Ponce-Peña, Patricia
Highlights: Suicide is associated with dysfunction of the serotonin neurotransmission system. Some serotonin-related genes such as MAOA and HTR2A have been associated with risk for suicide. Compare the expression of both genes in the brain of suicides completers from a Mexican population. Discusses molecular implications of both genes in the postmortem brain of suicides completers. Abstract: Objective: The main aim of the current study was to investigate whether the expression levels of the HTR2A and MAOA genes are altered in the postmortem brain of suicide victims from Mexican population. Methods: On the basis of a case– control study, we examined the expression levels of HTR2A and MAOA genes in the postmortem prefrontal cortex (Brodmann area 8/9) and hypothalamus (ventromedial nucleus) tissues from 20 suicide victims and 20 control subjects from a Mexican population. Gene-expression profile quantification was carried out by qPCR and determined by the 2 - Δ Δ C t method. Results: In suicide victims, the expression levels of the HTR2A gene were significantly higher in the prefrontal cortex. In contrast, the expression of the MAOA gene in the hypothalamus of the suicide victims was significantly higher than in the control subjects. These results were consistent regardless of age, sex, postmortem interval, or pH of brain tissue. Conclusion: The evidence suggests that the pattern of differential expression of HTR2A and MAOA genes in the brain may be involved in suicide, providing a possible molecular basis for the brain abnormalities in suicide victims.